Respuesta :
Answer:
Step 2
Step-by-step explanation:
The quadratic formula is given by [tex]x=-b+-\frac{\sqrt{b^{2}-4ac } }{2a}[/tex]
Our equation is y = 2x²-x-6
So here our a = 2, b = -1, and c = -6
We can now plug these numbers into our formula
[tex]x= -(-1) +-\frac{\sqrt{(-1)^{2}-4(2)(-6) } }{2(2)} = 1 +-\frac{\sqrt{1+24} }{4} = 1+-\frac{\sqrt{25} }{4}[/tex]
Step 2 is incorrect because it states that "x equals the negative of negative 1 plus or minus the square root of negative one plus forty-eight all over two times 2."
The correct statement would be "x equals the negative of negative 1 plus or minus the square root of positive one plus forty-eight all over two times 2.", because the square of a negative is positive, resulting in a positive one.
Since this step is incorrect, the steps after are also incorrect, but Harry went wrong at Step 2
Answer:
The above answer is correct.
Step-by-step explanation:
I got it right on the test